A study on the factors that affect training motivation among employees in Intech Tebrau, Johor / Muhamad Akmal Syazwan Sukereman and Nur Shaheeda Miswadi - Sukereman, Muhamad Akmal Syazwan; Miswadi, Nur Shaheeda (2014)
Operating a business with employees who have the skills and knowledge to stay productive is dependent upon a few factors. One of the biggest is developing and implementing successful training program that can teach employees and capitalize on their talents. By that, organization has play as important role in order to develop a successful training program through enhance the level of motivation of employees towards training program that they perceived. Training programs are assisting in transferring skills and know-how needed by the employees to make job done well from experts. Present research study focus on the factors that affect training motivation among employees in INTECH Tebrau, Johor which are social support, organizational commitment and clarity of a career goal. The research has been conducted among 110 employees from Part Production 1 department by using convenient sampling method. Result by using multiple regression test in this study was shown organizational commitment is the most influential factor to the training motivation perceived by the employees in INTECH Tebrau, Johor. Some other future recommendations have been discussed for further study.